IN-VITRO HEMODYNAMICS EVALUATION OF PROLAPSE AND PERFORATED MITRAL VALVE MODEL - Rudiyanto, Philman Jong; Mohamad Ikhwan, Kori; Kahar, Osman; Muhammad Noor Afiq Witri, Muhammad Yazid; Ahmad Zahran, Md. Khudzari (Longe Medikal Sdn Bhd, 2025)
The mitral valve is one of the important parts of the heart valve that prevents blood from regurgitating into the left atrium. Mitral regurgitation is the most common cause of regurgitation, affecting approximately 176 million people worldwide and 2-3% of the general population. Flow dynamics parameters are important for evaluating regurgitation severity, which can be done throughflow simulation. However, there are limited open-access datasets available for validating the simulated output. This paper presented an experimental setup that can serve as a validation tool for flow simulation output. Thein-vitro setup was tested by evaluating flow behaviour through a defective mitral heart valve. The results show consistent readings validated against published data. The correlation between flow rate and the pressure difference between the left ventricle and the left atrium follows the principles of fluid dynamics for flow through an orifice. Hence, this invitro setup can be used as a validation tool for flow simulation results, especially for heart valves